APLIKASI BIOTEKNOLOGI PADA KULTUR INVITRO MANGGA (MANGIFERA INDICA L.) - Husen, Syarief (Jurnal Bestari, 2001)
An applying biotechnology within mango culture in vitro is very useful to propagate mango micro plant, preserve germ-plasm, and improve plant genes through genetic engineering. The obstacle of mango culture in vitro has not been found an efficient method to produce mango plantlet, but somatic embryogenesis contribute to produce mango seed. To avoid browning and callus induction is the first most important step of mango somatic embryogenesis. The research findings indicates B-5 media within adding cinetin 1.2 and 3 mg/I produces embryogenesis and noduled callus compact is more than MS media with the same additional cinetin. Embryo somatic can induce in 13-5 media within the extra zeatin 0.25, 0.50, 0.75, and 1.0